An Indepth Analysis of Variables Affecting Post Purchase Cognitive Dissonance (Global Journal of Management and Business Research, 2012)
The research paper emphasizes on the need of assessing those variables which are responsible for affecting the levels of cognitive dissonance in the consumer behaviour. The paper signifies the impact that the family and friends have in the post purchase dissonance levels of the consumer. The results revealed that more the influence of family and friends in the decision making process, more degrees of dissonance will be felt by the consumer. The paper also depicts that the personality of the shopper would also affect the levels of dissonance. The confident shopper would experience lesser level of dissonance whereas a confused shopper would experience lower level of dissonance. Likewise, the purpose for which the product is to be used will also have an impact on the levels of dissonance. If the product is being purchased for some special purpose, then the dissonance level would be higher.
Keywords: Post Purchase; Cognitive Dissonance